Images of Justice: Contemporary Art in Retfærd. Nordic Journal of Law and Justice - Hammerslev, Ole (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
Many of the texts written about the relationship between law and art have background in the perception of art that existed before the manifestation of idea based and conceptual art in the 1960s. By contrast, this paper examines how contemporary art visually portrays justice from a variety of themes and aesthetic expressions. It takes background in cover pages of a Nordic journal Retfærd. Nordic Journal of Law and Justice, which has exhibited contemporary art works since 2006. The paper discusses artworks that represent both thematic and aesthetic down strokes, to illustrate the variety in the artists’ and art’s engagement with law. Moreover, since all the artworks are contemporary, they illustrate issues of societal concern, not least images about the wars in the aftermath of the terror attacks on 9/11, identity formation and commerce.